INSTITUTIONAL AND RESOURCE DEPENDENCE DETERMINANTS OF RESPONSIVENESS TO WORK-FAMILY ISSUES. - Ingram, P.; Simons, T. (Academy of Management Journal, 1995)
Whether and how organizations choose strategies that address pressures from both their exchange and the institutional environments has recently become a central question in organization theory. We ...